Dramatic changes in gene expression in different forms of Crithidia fasciculata reveal potential mechanisms for insect-specific adhesion in kinetoplastid parasites. - John N Filosa; Corbett T Berry; Gordon Ruthel; Stephen M Beverley; Wesley C Warren; Chad Tomlinson; Peter J Myler; Elizabeth A Dudkin; Megan L Povelones; Michael Povelones (Public Library of Science (PLoS), 2019)
Kinetoplastids are a group of parasites that includes several medically-important species. These human-infective species are transmitted by insect vectors in which the parasites undergo specific developmental transformations. For each species, this includes a stage in which parasites adhere to insect tissue via a hemidesmosome-like structure. Although this structure has been described morphologically, it has never been molecularly characterized. We are using Crithidia fasciculata, an insect parasite that produces large numbers of adherent parasites inside its mosquito host, as a model kinetoplastid to investigate both the mechanism of adherence and the signals required for differentiation to an adherent form. An advantage of C. fasciculata is that adherent parasites can be generated both in vitro, allowing a direct comparison to cultured swimming forms, as well as in vivo within the mosquito. Using RNAseq, we identify genes associated with adherence in C. fasciculata. As almost all of these genes have orthologs in other kinetoplastid species, our findings may reveal shared mechanisms of adherence, allowing investigation of a crucial step in parasite development and disease transmission. In addition, dual-RNAseq allowed us to explore the interaction between the parasites and the mosquito. Although the infection is well-tolerated, anti-microbial peptides and other components of the mosquito innate immune system are upregulated. Our findings indicate that C. fasciculata is a powerful model system for probing kinetoplastid-insect interactions.